Advancing Engineering Innovation through Project-Based Learning: A Qualitative Analysis of Experimental Applications in Indian Secondary Education - Singh, Vikram (International Journal Education and Computer Studies (IJECS), 2025)
Project-Based Learning (PBL) is an active and constructive approach to engineering education in which students are asked to work on problems without predetermined solutions in a problem-solving context. This paper has attempted to investigate the potential impact of PBL on the development of necessary engineering competencies in Indian school students, who constitute a crucial part of the country's potential innovative power base. Using the Hindi versions of 111 science and engineering project documents, this study qualitatively analyzed three of them to examine the projects—Building a Simple Electric Motor, Investigating Sliding Friction on an Inclined Plane, and Designing a Hydrometer Using Plastic Balls. The findings lead to the conclusion that these projects indeed embody fundamental engineering concepts such as electromagnetism, mechanics, and fluid dynamics, while fostering technical competency, creativity, and cooperative problem-solving as reflected in their design structure and projected outcomes. However, substantial barriers to implementing this reform in the Indian context exist, such as resource constraints, an exam-oriented curriculum, and inadequate teacher preparation, as demonstrated by the analysis. The study argues that PBL is a powerful pedagogical tool for transforming engineering education in developing countries, while suggesting relevant measures such as teacher training, curriculum inclusion, policy advocacy for experiential learning, and industry collaboration in these countries to address these challenges. In conclusion, this study highlights the potential of PBL to foster innovation among future engineering graduates in India, a relevant contribution to the national education agenda in the National Education Policy (NEP) 2020 as well as global discussions on experiential learning